The specifics of the President of the Republic of Kazakhstan as the subject of a legislative initiative. (Journal of actual problems of jurisprudence, 2016)
This article discusses the legal regulation of the legislative initiative right of the President of Kazakhstan, forms and procedures for its implementation. The article also presents issues of the draftlegislation introduced by the President of the Parliament RK, as well as the procedure for its application.
Keywords: Constitution; the President; the Parliament; the legislative initiative; law; legislative activity; legislator; deputy